Financial Literacy Planning for Homestay Management Activities in Coastal Tourism Areas - Sudarmi Sudarmi (Newinera Publisher, 2024)
This research aims to analyze the influence of financial literacy on the intention to improve performance and sustainability of homestay operators in Pinrang Regency. Using the Theory of Planned Behavior (TPB), the study explores how financial literacy affects attitudes toward behavior, subjective norms, perceived behavior control, and their impact on the operators' intention to enhance performance and sustainability. Results show that financial literacy significantly influences attitudes toward behavior, perceived behavior control, and subjective norms of homestay operators. The intention to improve performance and sustainability is positively influenced by attitudes and perceived behavior control, while subjective norms have no significant impact. These findings highlight the crucial role of financial literacy in supporting homestay performance and sustainability in Pinrang Regency, emphasizing the need for continued support from relevant stakeholders.